Measuring mental workload in IIR user studies with fNIRS - Wilson, Max L.; Alsuraykh, Norah; Maior, Horia A. (2017)
Gathering neuro-physiological data during user studies, and analysing the continuous data they produce, typically involves making a tradeoff between detail and practical utility. is paper describes our long-term work-in-progress towards developing study protocols for using functional Near-InfraRed Spectroscopy (fNIRS) with the aim of finding the ideal balance in this tradeoff. Our results show that fNIRS can be easily used in normal IIR user study conditions, is tolerant of minor movement artefacts (including speaking), and can still determine mental workload differences between different user interfaces designed for the same task.